2017
DOI: 10.5194/angeo-35-691-2017
|View full text |Cite
|
Sign up to set email alerts
|

Errors in wind resource and energy yield assessments based on the Weibull distribution

Abstract: Abstract. The methodology used in wind resource assessments often relies on modeling the wind-speed statistics using a Weibull distribution. In spite of its common use, this distribution has been shown to not always accurately model real wind-speed distributions. Very few studies have examined the arising errors in power outputs, using either observed power productions or theoretical power curves. This article focuses on France, using surface wind measurements at 89 locations covering all regions of the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Its validity for application to wind speed modeling is argued and shown not to be the best to properly describe the wind speed characteristics of certain times and locations [8]. Some probability distributions that have also been deployed for assessment of wind speed include generalized extreme value distribution of Gumbel (Type I), Fréchet (Type II) and reverse Weibull (Type III) [6] and mixed Rayleigh-Rice distribution [12]. Other non-Weibull distribution applications are found in [22,16,25].…”
Section: Wind Speed Modelingmentioning
confidence: 99%
“…Its validity for application to wind speed modeling is argued and shown not to be the best to properly describe the wind speed characteristics of certain times and locations [8]. Some probability distributions that have also been deployed for assessment of wind speed include generalized extreme value distribution of Gumbel (Type I), Fréchet (Type II) and reverse Weibull (Type III) [6] and mixed Rayleigh-Rice distribution [12]. Other non-Weibull distribution applications are found in [22,16,25].…”
Section: Wind Speed Modelingmentioning
confidence: 99%
“…It is also observed that the Wind Atlas Analysis and Application Program (WAsP) (official website: http://www.WAsP.dk) method has a limited use in such studies. Most of the studies using the WAsP method through the WAsP software are not comparing it to other methods [34,35], but see [36]. In the current study, a selection of methods from the literature was used for the estimation of Weibull parameters..…”
Section: Distribution Analysismentioning
confidence: 99%
“…The authors then demonstrate how this method can be used to add uncertainty information to economic feasibility studies. Jourdier and Drobinski (2017) note that wind resource assessments often make the assumption that wind speed distributions follow a Weibull curve, and they evaluate the error contained in that assumption. They use sample wind turbine power curves to demonstrate the important difference between an evaluation of the wind resource power as compared with the actual wind turbine output.…”
Section: Review Of Literaturementioning
confidence: 99%